Genetic polymorphism and the risk of diabetic foot: a bibliometric analysis from 2011-2021 - Maliza, Rita; Irham, Lalu Muhammad; Pradika, Jaka; Pratama, Kharisma; Dania, Haafizah; Arya, Bramadi; Perwitasari, Dyah Aryani (International Journal of Public Health Science (IJPHS), 2023)
Diabetic foot ulcer (DFU) has been associated with genetic and environmental factors, which could potentially have a role in DFU development. Single nucleotide polymorphisms (SNPs) in genes linked to DFU, including inflammation. Bibliometric studies on the SNP on genes affecting DFU still have not been evaluated. This study aims to depict bibliographically and understand the topic trend of genetic polymorphism and the risk of DFU publications. A bibliometric methodology was applied in this study. The data were extracted through the Scopus database from 2011 to 2021. VOS viewer was used to classify and summarize Scopus articles. The 35 articles were evaluated. India topped the list of countries with the most publications, and Tehran University of Medical Sciences was the primary institution. Singh K and his team were the first contributing authors with 44 citations. Keywords analysis indicated that the research hotspots were DFU, type 2 diabetes mellitus (T2DM), diabetic foot ulcers, polymorphisms, hypoxia, vascular endothelial growth factor (VEGF), diabetic foot, diabetes mellitus, and oxidative stress. This study summarizes the current state, trends in genetic polymorphism and risk with DFU research. It may provide researchers with insight into the genetic polymorphism and risk associated with DFU research, as well as useful information for identifying possible collaborators and partner institutions.